The Influence of Limited Infrastructure and Learning Facilities on Students' Learning Motivation and Academic Achievement - Deca Anisa Putri; Chantika Aprilia; Rizka Azzahra, Zypha; Repita Erpalina; Fajar Ken Finada (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2025)
Background: Many secondary schools face limited infrastructure and learning resources, which are suspected to reduce student motivation and academic achievement. However, integrated empirical studies are still limited. This study examines the effect of limited infrastructure and learning resources on learning motivation and academic achievement simultaneously.Methods: A quantitative correlational design involving 120 junior high school students selected using proportionate stratified random sampling. Data were collected through a valid Likert-scale questionnaire and report card grades from the odd semester of 2024/2025, then analyzed using multiple linear regression.Results: Limited infrastructure (β = –0.312; p < 0.001) and limited learning resources (β = –0.278; p = 0.002) significantly reduced learning motivation (R² = 0.46). Both also reduced academic achievement (β infra = –0.294; p = 0.001, β sarana = –0.336; p < 0.001), with a simultaneous contribution of 57%. As many as 5.8% of students maintain high achievement thanks to independence and family support.Conclusion: The quality of infrastructure and learning facilities is a key determinant of motivation and academic achievement. Improving educational facilities is a priority strategy to support equitable learning quality.